The DuBois-Reymond differential inclusion for autonomous optimal control problems with pointwise-constrained derivatives - Carlota, Clara (2011)
We prove validity of the classical DuBois-Reymond differential inclusion for solutions of autonomous optimal control problems with pointwise-constrained derivatives.